Everyday Perseverance & Meaningful Toil: Mapping the (In)distinguishable Process of Recovery Post-hurricane Katrina, New Orleans, Louisiana - (:unkn) unknown (My University, 2019)
For nearly a century, anthropological scholarship on disaster has contributed to advancing emergency preparation and management, however examination focusing on survivors’ return and responses in the aftermath of catastrophe, specifically the ways in which residents work to recover—if at all—remains far from comprehensive, especially in urban, post-industrial settings. Following calamity, what remains? What is disturbed? What becomes reconstructed? Who repairs the tattered social fabric or restores the built environment? And how do these processes transpire? These questions summarize the research interests of this dissertation, which examines the place-making practices not of experts or administrators, but, rather, those enacted by (extra) ordinary community members of the Lower Ninth Ward post-Hurricane Katrina New Orleans. Specifically, this investigation of place-making in the aftermath of disaster focuses on four main practices: residents-led tours, civic engagement, community establishments/ businesses, and commemorative events. Although these practices and the places residents’ make through these efforts entail ephemerality, I maintain that this toil is particularly meaningful in distinguishing how survivors confront loss, disorientation, and trauma while simultaneously cultivating healing in their lives, livelihoods, and landscape. The findings of this project include that the multiple and fragmentary practices of residents promote a return to the everyday in Katrina's wake and these commingled ways of operating, reveal the adaptive and empowering response of collective autonomy. People's sense of place is a well-studied theme by scholars from diverse disciplines, yet there is much to learn from analyzing this critical dimension of the human condition within a post-disaster context. In gathering data with both long-established ethnographic techniques (prolonged ethnographic fieldwork and participant observation) and innovative, geographic information systems (GIS), this research makes a distinct contribution to the anthropological knowledge and literature focused on sociocultural and spatiotemporal transformation following disasters. This cross-disciplinary approach serves as a novel means for anthropologists to holistically explore the intertwining dynamics involved when previously familiar aspects of life become significantly disrupted including, but are not limited to: environmental, linguistic, historic, political, spiritual, and symbolic. Consideration of these aspects of the lives of those living in the wake of disaster illuminates complexity of remaking home while legitimizing the desire to return to it – especially urgent matters in this era of global climate change.
Keywords: Counter-mapping; Disaster; Hurriane Katrina; New Orleans; Place-making; Recovery